Developing a Digital and Maqasid-Based Waqf Governance Framework: A Systematic Literature Review - Muhammad Syahrullah; Muhammad Lisman (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: In order to improve waqf institutions' sustainability, accountability, and openness, good corporate governance, or GCG, has become essential. Despite the increasing amount of research, the studies that have already been done are still dispersed and mainly concentrate on specific aspects of governance rather than offering an integrated framework that takes stakeholder viewpoints, digital transformation, and Islamic values into account. The objective of this study is to provide a thorough conceptual framework and conduct a methodical evaluation of the literature on GCG in waqf organizations. Methods: The PRISMA 2020 guidelines were followed in this study's Systematic Literature Review (SLR). Using predetermined inclusion and exclusion criteria, pertinent papers published between 2016 and 2026 were extracted from the Scopus database. To find governance themes and synthesize conceptual links, the chosen studies were examined using grounded theory methodologies that included open coding, axial coding, and selective coding. Results: Governance Principles, Islamic Governance, Digital Governance, Stakeholder Governance, and Governance Outcomes are the five fundamental components of governance that were recognized by the review. The results show that while emerging themes like digital governance, artificial intelligence, blockchain, and maqasid al-shariah have grown in significance in boosting institutional performance and public trust, transparency and accountability continue to be the predominant governance principles. An Integrated Good Corporate Governance Framework for Sustainable Waqf Institutions, which blends traditional governance concepts with Islamic ethical values, digital innovation, stakeholder involvement, and sustainability, is the outcome of the synthesis. Conclusion and suggestion: The theory and practice of waqf governance are advanced by this study's comprehensive governance structure. Future studies should use quantitative or mixed-method approaches to experimentally validate the suggested framework in various institutional and national contexts.